(untitled) (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
Genu varum is a growth disorder of the lower limbs characterized by an abnormal angular deviation between the knee and femur due to rotational changes in the knee joint. Factors such as lower limb development, pathological conditions, and genetic predisposition may influence the occurrence of this condition. This study aimed to identify the inheritance pattern of genu varum through family pedigree analysis in the Jambi region and to examine the influence of environmental factors on its incidence within the local community. This research employed a descriptive cross-sectional design. Data were collected in Jambi City from September to October 2025. Four families were purposively selected based on the criterion that at least one family member had been diagnosed with genu varum. Family history data were used to construct pedigrees, and clinical measurements were performed by assessing intercondylar distance. The results indicated that although genetic factors play a significant role, variations in inheritance tendencies were observed among the four families studied.